1991
DOI: 10.1200/jco.1991.9.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine: a new agent with marked cytoreductive activity in untreated chronic lymphocytic leukemia.

Abstract: Thirty-three patients with chronic lymphocytic leukemia (CLL) with advanced Rai stage (III-IV) or progressive Rai stage (0-II) disease were treated with fludarabine as a single agent. Eleven patients (33%) obtained a complete remission (CR), 13 (39%) a clinical CR with residual nodules as the only evidence of disease (nodular partial remission [PR]), and two patients (6%) achieved a PR for a total response rate of 79%. Response was rapid, usually occurring after three to six courses of treatment. The major mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
180
1
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(188 citation statements)
references
References 14 publications
6
180
1
1
Order By: Relevance
“…Despite this unfavourable setting, undoubted activity has been demonstrated in both CLL and follicular NHL, in accordance with other results (Grever et al, 1986;Leiby et al, 1987;Redman et al, 1988;Keating et al, 1989a;Hochster & Cassileth, 1990;Puccio et al, 1990).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Despite this unfavourable setting, undoubted activity has been demonstrated in both CLL and follicular NHL, in accordance with other results (Grever et al, 1986;Leiby et al, 1987;Redman et al, 1988;Keating et al, 1989a;Hochster & Cassileth, 1990;Puccio et al, 1990).…”
Section: Discussionsupporting
confidence: 79%
“…An active triphosphate metabolite is formed intracellularly which intereferes with DNA synthesis by inhibition of DNA polymerase and ribonucleotide reductase (Huang & Plunkett, 1986 murine models has been borne out in Phase I and II testing (Hutton et al, 1984;Spriggs et al, 1986;Champagne et al, 1987). At a dose of < 125 mg/m2/course, significant activity, with response rates of 60% and more, has been reported in CLL and follicular NHL, with some modest benefit in diffuse low grade lymphoma (Grever et al, 1986;Leiby et al, 1987;Redman et al, 1988' Hochster & Cassileth, 1990Keating et al, 1989a;Puccio et al, 1990). Fludarabine is reported to be well tolerated at such doses, the toxicity in these studies being predominantly infective episodes arising from myelosuppresion.…”
mentioning
confidence: 99%
“…Nodular responses are not separately reported and therefore the incidence of CR in these reports may include patients with nodular responses. Our result of CR plus nodular responses in 16% of patients may be consistent with the 21% incidence of CR in the European trial 24 and 27% CRs reported by Rai et al 19 These results contrast with the report by Keating et al, 9 in which 33% of patients achieved a CR to single agent fludarabine. The reported differences in the frequency of CR may be due to several reasons, including patient selection, criteria for response, and fludarabine dose delivered.…”
Section: Discussioncontrasting
confidence: 57%
“…1,2 In general, these responses are not durable and patients ultimately succumb to progressive resistant disease. The introduction of three new agents; fludarabine, 3,4 cladribine 5,6 and pentostatin 7,8 has renewed interest in aggressive therapy of selected patients with CLL. Of these drugs, fludarabine has been the most widely studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation